Chorangioma in Multiparous Aged: Clinical Case - Rodríguez-Villalobos, Paula Cecilia; Colli-Chan, Alejandro; Villalobos-Rodríguez, Alejandro Lenin; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2022)
Introduction: Chorangioma is a vascular tumor of placental origin that belongs to the group of vascular hemangiomas, the first report of this tumor was due to Clark in 1798; it is the most common primary non-trophoblastic placental tumor of vascular origin; Due to the few cases reported in the literature, the case treated at our hospital is reported. Clinical case: A 37-year-old female has been admitted with the following history: menarche at 12 years of age, IVSA at 13 years of age Gesta 3, Para 2, Caesarean sections 0, Abortions 0, FUP 7 years ago, FPP 06-19-2022 with two follow-up visits prenatal; US pregnancy of 34 SDG, FPP 05-30-2022, Weight 2,250 g. The patient presents obstetric pain of one hour of evolution and, a pregnancy of 35 WG plus labor in the latent phase was diagnosed. Eutocic delivery without complications and placental tumor observed. Conclusions: This tumor teaches us that the placental evaluation by ultrasound-doppler control is essential to detect this type of tumor that when they are small, generally goes unnoticed.